2016
DOI: 10.1107/s2053229616001509
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and crystal structure of a two-dimensional sodium coordination polymer of 4,4′-(diazenediyl)bis(1H-1,2,4-triazol-5-one)

Abstract: The crystal engineering of coordination polymers has aroused interest due to their structural versatility, unique properties and applications in different areas of science. The selection of appropriate ligands as building blocks is critical in order to afford a range of topologies. Alkali metal cations are known for their mainly ionic chemistry in aqueous media. Their coordination number varies depending on the size of the binding partners, and on the electrostatic interaction between the ligands and the metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Coordination polymers incorporating Na + nodes are very rare due to their tendency to accept a large number of solvent molecules into their coordination sphere. Nonetheless, these materials have recently emerged as promising candidates for sodium ion batteries (SIB) . Yaghi et al reported two Na-based MOFs that are formed from stable Na-metal oxide two-dimensional (2-D) sheets connected by a tetratopic linker to form three-dimensional (3-D) architectures .…”
Section: Introductionmentioning
confidence: 99%
“…Coordination polymers incorporating Na + nodes are very rare due to their tendency to accept a large number of solvent molecules into their coordination sphere. Nonetheless, these materials have recently emerged as promising candidates for sodium ion batteries (SIB) . Yaghi et al reported two Na-based MOFs that are formed from stable Na-metal oxide two-dimensional (2-D) sheets connected by a tetratopic linker to form three-dimensional (3-D) architectures .…”
Section: Introductionmentioning
confidence: 99%